2019
DOI: 10.1002/nop2.333
|View full text |Cite
|
Sign up to set email alerts
|

Effect of foot care interventions for older adults using day care services

Abstract: AimThis study explored the prevalence of foot problems among older adults and the effectiveness of foot care interventions for improving toe‐gap force and foot flexibility. Foot problems are very common among people aged 65 years and older. However, the effects of foot care interventions on components underlying these issues (i.e., toe‐gap force and foot flexibility) are unclear.DesignThis was a quasi‐experimental study.MethodsEighteen older adults were divided into three groups: medical foot care intervention… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 34 publications
0
9
0
1
Order By: Relevance
“…In this study, no signi cant between-group difference was found in the foot morphology, including for hallux valgus; even in the multiple logistic regression analysis, foot morphology was not among the signi cant factors. The prevalence of hallux valgus detected on radiographs in older Japanese men and women living in the community was 28.4% (3) and that in day care service users was > 50% (4). In this study, hallux valgus was found in about half of the older participants who needed some assistance with activities of daily living and are undergoing or had received ambulatory rehabilitation in a long-term care health facility.…”
Section: Discussionmentioning
confidence: 52%
See 1 more Smart Citation
“…In this study, no signi cant between-group difference was found in the foot morphology, including for hallux valgus; even in the multiple logistic regression analysis, foot morphology was not among the signi cant factors. The prevalence of hallux valgus detected on radiographs in older Japanese men and women living in the community was 28.4% (3) and that in day care service users was > 50% (4). In this study, hallux valgus was found in about half of the older participants who needed some assistance with activities of daily living and are undergoing or had received ambulatory rehabilitation in a long-term care health facility.…”
Section: Discussionmentioning
confidence: 52%
“…Hallux valgus was found in 28.4% of older Japanese people living in the community (3). Furthermore, more than 50% of 18 older adults who use day care services for assistance in daily life have hallux valgus (4). Although many studies have focused on the foot morphology of community-dwelling older people, there are only a few reports about this issue in older people requiring long-term care.…”
Section: Introductionmentioning
confidence: 99%
“…In the Japanese system, older people use two types of insurance system to obtain health services: the national insurance and long‐term care insurance (Fujii, 2019). Nurses and care workers who work at in‐home service providers play a great role in supporting clients who need some assistance in relation to maintaining their health, the daily activities of living and simple rehabilitation.…”
Section: Introductionmentioning
confidence: 99%
“…Community-dwelling older people in Japan experience various health conditions, with some requiring assistance for medical treatment or activities of daily living and some using long-term care insurance [3]. Older people may request foot care from NCWs or may refuse to seek active care [4] despite the high prevalence of foot problems in this population.…”
Section: Introductionmentioning
confidence: 99%
“…Older people may request foot care from NCWs or may refuse to seek active care [4] despite the high prevalence of foot problems in this population. However, studies on this topic are limited [3,5].…”
Section: Introductionmentioning
confidence: 99%